Academic Motivation Predicted by Growth Mindset and Parental Support - Yang, Yaliu; Chen, Liang (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to investigate the predictive roles of growth mindset and perceived parental support on academic motivation among high school students in China. Methods and Materials: A correlational descriptive design was employed, and the sample included 499 high school students selected based on the Morgan and Krejcie (1970) sample size table. Participants completed standardized instruments: the Academic Motivation Scale (AMS), the Growth Mindset Scale, and the Perceived Parental Autonomy Support Scale (P-PASS). Descriptive statistics, Pearson correlation, and linear regression analyses were conducted using SPSS-27 to examine the relationships and predictive power of the independent variables on academic motivation. Findings: Descriptive results showed that students reported high levels of academic motivation (M = 5.41, SD = 0.72), growth mindset (M = 4.83, SD = 0.65), and parental support (M = 5.12, SD = 0.69). Pearson correlation analysis revealed significant positive relationships between academic motivation and growth mindset (r = .61, p < .001), as well as between academic motivation and parental support (r = .55, p < .001). Linear regression results indicated that growth mindset (β = .42, p < .001) and parental support (β = .36, p < .001) were significant predictors of academic motivation. The regression model was statistically significant (F(2, 496) = 202.14, p < .001), with an R² value of .45, indicating that the two predictors jointly explained 45% of the variance in academic motivation. Conclusion: The findings demonstrate that both growth mindset and perceived parental support significantly contribute to the academic motivation of high school students.